Sorry to burst your bubble - Chew, Rachel Jia Hui (Nanyang Technological University, 2023)
Stereotypes and bias often take a nuanced way in showing itself in our modern community. I think we all remember that age old joke on men being the more emotional gender, right? Often, these casual remarks and jokes are gleaned over by society, with justifications by the naysayer that they have been factually supported and proven for years. Recent spotlight on policies, such as the White Paper, has ignited growing conversations on gender bias in our Singaporean society, particularly on women, the workplace and how they navigate the double bind bias. It is important to recognise that bias can occur in workspaces of any kind, and that bias can come from anyone regardless of gender identity.